The rationales behind free and proprietary software selection in organisations - Sticklen, D.; Issa, Theodora (IADIS Press, 2010)
The aim of this paper is to critically examine the important assumptions behind the software-selection function in organisations. Software is incorporated in many situations within enterprises due to its unique ability to efficiently and effectively augment business functions and processes. Proprietary software with its inherent advantages and disadvantages remains dominant over "Free and Open-Source Software" (FOSS) in a large number of cases. However, the arrival of cloud-computing almost certainly mandates a heterogeneous software environment. Open standards, upon which most FOSS is based promotes the free exchange of information, a founding requirement of the systems embedded in organisations. Despie evidence to the contrary, the fact that FOSS is also available at low financial cost, combined with the benefits implicit in facilitating inter-process communication supports the view that it would be attractive to organisations.This paper approaches the paradoxical situation by examining the relevant literature in a broad number of disciplines. An important aspect examined is the roles that management, and in particular the executive, play in the software-selection functio. It is on the basis of these findings that the rationales of use for both proprietry and FOSS are discussed in a multi-disciplinary context. Understanding the rationales behind the software-selection function may provide academics and practitioners with insight into what many would consider an ICT-centric problem. However, by abstratcting to the managment context, as opposed to the technical context, the organisational issues surrounding both proprietary software and FOSS adoption are counter-intuitively brought to the forefront.